FRI0038 Release of peptidylarginine deiminiase 2 from activated neutrophils. (15th June 2017) - Steffensen, MA; Damgaard, D; Bassi, M; Nielsen, CH
Abstract : Background: Extracellular citrullination catalyzed by peptidylarginine deiminase (PAD) is thought to play a central role in the pathogenesis of rheumatoid arthritis. Neutrophils are a major reservoir of PAD2 and PAD4. Cellular release of PAD2 and PAD4 is usually considered a consequence of cell death. Objectives: We aimed to determine if PAD2 can be released from live, activated neutrophils as an active process. Methods: Whole blood cells were purified from healthy blood were stimulated with phorbol 12-myristate 13-acetate (PMA). To capture PAD2 released from neutrophils and detect it by flow cytometry, we used biotinylated anti-CD15 and anti-PAD2 (mAb DN6) mAbs linked by streptavidin, and a different PE-labelled anti-PAD2 amtibody (mAb DN2). In addition, intracellular PAD2 was quantified by intracellular staining with PE-anti-PAD2. PAD2 released from leukocytes and subcellular fractions of human granulocytes were assessed for content of PAD2 using an in-house luminex-based assay. Results: On incubation of whole blood cells with PMA, PAD2 was detectable in the supernatants after 30 minutes, and levels increased thereafter in parallel with increasing cell death. However, using PAD2 catch reagent, we found that live neutrophils released PAD2 in the 30 minutes after stimulation. Intracellular staining for PAD2 showed that the content of PAD2 in live neutrophils decreased correspondingly. Upon subcellular fractioning of granulocytes, the majority of PAD2 was found in cytosol and, in 25 times lower quantities, in the fraction containing plasma membranes and secretory vesicles. Sparse amounts of PAD2 were also observed in gelatinase granules. Conclusions: In conclusion, PAD2 can be released from live, activated neutrophils, which may contribute to extracellular citrullination and thereby play a role in driving inflammatory processes in RA patients with immune responses to citrullinated proteins. Disclosure of Interest: None declared